Understanding trend inflation through the lens of the goods and services sectors - Yunjong Eo; Luis Uzeda; Benjamin Wong (Bank of Canada, 2020)
We distinguish between the goods and services sectors in an otherwise standard unobserved components model of US inflation. Our main finding is that, while both sectors used to contribute to the overall variation in aggregate trend inflation, since the 1990s this variation has been driven almost entirely by the services sector. Two changes in sector-specific inflation dynamics are responsible for this finding: (i) a large fall in the variance of trend goods inflation; and (ii) the disappearance of comovement between trend goods and trend services inflation. Extensions to our baseline analysis by excluding energy prices and decomposing trend inflation into a common and a relative price component suggest a possible role of monetary policy in explaining our empirical findings. We also document similar changes in inflation dynamics internationally when extending our analysis to Australia and Canada.
Keywords: C11; C32; E31; E52; 330; Econometric and statistical methods; Transmission of monetary policy; Inflation and prices